2014
DOI: 10.1093/bja/aeu054
|View full text |Cite
|
Sign up to set email alerts
|

Low intraoperative tidal volume ventilation with minimal PEEP is associated with increased mortality

Abstract: Use of low intraoperative TV with minimal PEEP is associated with an increased risk of 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 28 publications
6
109
1
7
Order By: Relevance
“…After carefully reading this retrospective study by Levin et al and previously published randomized controlled clinical trials, we agree with Levin and his colleagues that use of a low level PEEP without recruitment manoeuvres is one of the possible causes for their worse postoperative outcomes (8), because the use of low VT ventilation with low levels of PEEP can promote loss of lung aeration and atelectasis formation (4). Moreover, this study is a retrospective analysis using observational designs, which potentially introduces a number of confounding variables that a nonrandomized study may not have removed completely.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…After carefully reading this retrospective study by Levin et al and previously published randomized controlled clinical trials, we agree with Levin and his colleagues that use of a low level PEEP without recruitment manoeuvres is one of the possible causes for their worse postoperative outcomes (8), because the use of low VT ventilation with low levels of PEEP can promote loss of lung aeration and atelectasis formation (4). Moreover, this study is a retrospective analysis using observational designs, which potentially introduces a number of confounding variables that a nonrandomized study may not have removed completely.…”
supporting
confidence: 56%
“…Thus, the PROVHILO trial concluded that an intraoperative lung-protective ventilation strategy should include a low VT and low PEEP (≤2 cm H2O) (7). However, in a retrospective single-centre study of 29,343 patients receiving mechanical ventilation and undergoing general noncardiac surgeries under general anesthesia, Levin and his colleagues (8) showed that use of VT in the range applied in the PROVHILO trial published by The Lancet (7) and minimum levels of PEEP (median=4 cm H2O) were associated with an increase in 30-day mortality and prolongation of hospital stay.…”
mentioning
confidence: 99%
“…Indeed, LV t with low PEEP has been shown to actually increase mortality in surgical patients at high risk for ARDS. 28,29 Minimizing a Ventilation Injury Cost Function MV can be delivered in a near limitless variety of confi gurations according to the value of the various parameters that defi ne its characteristics. Th e parameters most commonly manipulated in patients with ARDS include V t (the current goal being 6 mL/kg ideal body weight), plateau pressure (the desired maximum being typically 30 cm H 2 O), and PEEP (the goal being to reduce derecruitment at the end of expiration).…”
Section: Patients Undergoing Major Surgerymentioning
confidence: 99%
“…Indeed, clinical studies have shown that early application of LV t ventilation with various levels of PEEP signifi cantly reduces the incidence of ARDS, presumably by reducing tissue overdistension in areas of stress concentration and by preventing RACE. 20,24,26,39,40 However, a recent study demonstrated that LV t alone applied to the normal lung during surgery in patients at high risk for developing ARDS was associated with increased mortality 28 and that LV t with high but not low PEEP increased postoperative pulmonary complications. 29 In contrast, Futier et al 26 showed that the combination of LV t , PEEP, and RMs signifi cantly reduced acute respiratory failure and mortality in patients undergoing major surgery.…”
Section: T Peep and Rmsmentioning
confidence: 99%
“…In 15 subjects with ARDS, Richard et al 25 demonstrated that low V T (6 mL/kg) with PEEP set at the lower inflection point was associated with significant alveolar derecruitment, which improved with application of a recruitment maneuver. More importantly, Levin et al 26 demonstrated an increased risk of 30-d mortality with low intraoperative V T and minimum PEEP in subjects without ARDS.…”
Section: Ards and Variability In Mechanical Ventilationmentioning
confidence: 98%